Komparasi Tujuan dan Standar Kurikulum Social Studies Sekolah Dasar Kanada dan Indonesia - I Nengah Suastika (Mahesa Research Center, 2021)
The curriculum has a strategic role in supporting teachers in carrying out the learning process and students in skills skills. Curriculum changes that have occurred in several countries such as Japan, South Korea, the United States, and Canada have shown encouraging results. It is proven that the implementation of the curriculum has brought changes, improvements and enhancements to the quality of education in the country. Based on studies conducted, the Social Science curriculum in Canada was created and developed based on subjects. The objectives of Canadian Primary School Social Studies are to provide an understanding of the basic concepts of Social Studies, develop the skills, strategies and habits of thought necessary for effective inquiry and communication, as well as to apply basic Social Science concepts, to a variety of learning tasks, and impart skills. to relate and apply the social studies obtained through social studies to the world outside the classroom. Meanwhile, the goal of elementary school social science in Indonesia is to lay the foundation of intelligence, knowledge, personality, noble morals, and skills to live independently and follow further education. The curriculum in Social Sciences Grades 1 to 6 in Canada, organizes learning in a set of basic concepts, namely systems and structures, interaction and interdependence, environment, change and sustainability, culture, and governance.